THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURSHIP INTEREST IN SHARIA BUSINESS MANAGEMENT STAIN MANDAILING NATAL - Vebri Sugiharto (Jurnal Education and Development, 2022)
This study aims to determine the effect of entrepreneurship education on entrepreneurial interest in Sharia Business Management STAIN Mandailing Natal students. This type of research is a quantitative research. The population of this study were students of Islamic Business Management STAIN Mandailing Natal class of 2019 and class of 2020. The sample in this study amounted to 50 students. Data were collected using a questionnaire and analyzed by simple linear regression with the help of Statistical Program Social Science (SPSS) version 20 for windows. The results showed that entrepreneurship education had a positive and significant effect on the entrepreneurial interest of Islamic Business Management students at STAIN Mandailing Natal. The magnitude of the influence of entrepreneurship education on students' interest in entrepreneurship is 78.6% while the remaining 21.4% is influenced by other factors.